Polyposis of gastrointestinal tract after COVID-19 mRNA vaccination: a report of two cases - Jun Ho Kim; Eun Hye Oh; Dong Soo Han (Korean Society of Gastrointestinal Endoscopy, 2024)
Cronkhite-Canada syndrome is a rare gastrointestinal polyposis syndrome with distinctive clinical features and endoscopic findings. Diagnosis can be challenging without suspicion, and the disease carries high mortality due to complications such as infection, gastrointestinal bleeding, and malignancies. This paper presents two cases of Cronkhite-Canada syndrome occurring after coronavirus disease 2019 (COVID-19) mRNA vaccination. Both cases exhibited typical clinical findings, including hypogeusia, onychodystrophy, alopecia, and weight loss. Typical polyposis in the gastrointestinal tract was confirmed through endoscopies. As symptomatic treatment did not improve the symptoms, corticosteroids were administered, and symptoms and laboratory test results improved immediately. The patients improved upon corticosteroids tapering. These cases illustrate typical presentations of Cronkhite-Canada syndrome and the course of the disease following corticosteroid treatment. Additionally, they suggest the possibility that Cronkhite-Canada syndrome may be triggered by COVID-19 mRNA vaccination.